Production of Bioactive Peptides by Lactobacillus Species: From Gene to Application - Raveschot, Cyril; Cudennec, Benoit; Coutte, François; Flahaut, Christophe; Fremont, Marc; Drider, Djamel; Dhulster, Pascal (Frontiers in Microbiology, 2018)
To compensate for their amino acid auxotrophy, lactobacilli have developed the ability to hydrolyze proteins present in their environment. This proteolytic activity generates the free amino acids needed by the bacteria, but also a large variety of peptides, some of which are endowed with biological activities. These so-called “bioactive peptides” (BAPs) are interesting from nutrition and healthcare point of views. The use of lactic acid bacteria (LAB) such as lactobacilli is an effective strategy for production and valorization of new bioactive peptides. The proteolytic activity of lactobacilli is exerted in a strain- and species-dependent manner: each species exhibits different proteinase content, leading to a large variety of proteolytic activities. This underlines the high potential of Lactobacillus strains to produce novel hydrolysates and bioactive peptides of major interest. This review aims at discussing the potential of different Lactobacillus species to release bioactive peptides from fermentation media and processes. Strategies used for peptide production are presented. Additionally, we propose a methodology to select the most promising Lactobacillus strains as sources of bioactive peptides; this methodology combines conventional approaches and in silico analyses.